Bad news for Labour : antisemitism, the party and public belief - Philo, Greg; Berry, Mike; Schlosberg, Justin; Lerman, Antony; Miller, David (Pluto Press, 2019)
A groundbreaking study revealing how accusations of antisemitism damaged the British Labour Party under Jeremy Corbyn's leadership.